Pemanfaatan Lahan Sawah Pasca Panen di Desa Manjalling Kecamatan Ujung Loe Kabupaten Bulukumba - Muhammad Hilman Rosyidi; Mr. Jumadi; Abdul Rahman (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2022)
This study examines the form of post-harvest land use in Majelling Village, the constraints and strategies used by farmers in post-harvest land use, and the implications of post-harvest land use on the economy and ecology. Data collection techniques were carried out using observation, interviews and documentation methods involving 22 (twenty two) informants. The results showed that: (1) The form of land use post-harvest rice carried out by farmers by rotating crops with intercropped crops, namely secondary crops. (2) the obstacles encountered and have been going on for quite a long time, namely the problem of water supply to agricultural land being hampered. The strategy that farming communities apply to support the sustainability of their agriculture in the third planting season during the dry season is to see the suitability of plants and the selection of the best varieties. (3) The economic and ecological implications have a close relationship in improving the economy of farmers, with the selection of the right plants the selling value of the food commodities that farmers grow will increase, Ecologically by continuing to plant land during the dry season by rotating crops, it has an impact on stability in the environment. Soil pH and soil productivity are maintained.